La2O2CO3-Induced phase composition oscillation in La–Cu mixed oxides during repeated catalytic soot combustion. Issue 18 (3rd September 2019) - Zhao, Han; Li, Hongcheng; Gu, Yongwan; Zheng, Tingting; Zhao, Depeng; Xia, Wenzheng; Zhao, Yunkun; Chen, Hangrong
Abstract : La2 O2 CO3 -Induced phase composition oscillation between phase 1 (CuO + La2 O2 CO3 ) and phase 2 (La2 CuO4 ) in La–Cu mixed oxides during repeated catalytic soot combustion. Abstract : La–Cu mixed oxides, denoted as LaCuO- x ( x = 500, 650 and 800), were prepared by calcination at 500, 650 and 800 °C, respectively, with the same precursor. It was found that fresh LaCuO- x catalysts exhibit various phase compositions, and different phase evolutions occur in LaCuO- x during the repeated soot combustion tests. In particular, an interesting reversible phase evolution, i.e., La2 O2 CO3 + CuO ↔ La2 CuO4 + CO2, was observed in LaCuO-500 or -650. Various characterization methods including XRD, XPS, soot/CO/H2 -TPR, and thermal analysis, together with verification tests were designed and conducted to unveil the reasons behind the phase oscillation. A plausible mechanism was further proposed, emphasizing the vital role of La2 O2 CO3 -catalyzed CO formation in the phase oscillation in the repeated soot combustion tests.